The Effect of Public Communication, Youth Participation and Social Media on Community Receptions About Covid Pandemic in Village - Novila Indriawati; Ainur Rochmaniah (Universitas Muhammadiyah Sidoarjo, 2023)
Public perception of the Covid-19 pandemic is very diverse, people view events in their environment with different responses. Especially the response regarding the Covid-19 Pandemic in the Rw.06 Village area. Kalisampurno, from the various symptoms of Covid-19, people who were exposed to Covid-19 even died due to Covid-19. Therefore Rw.06 Village, Kalisampurno formed a team to help residents of Rw.06 deal with the Covid-19 Pandemic in the Rw.06 neighborhood. Starting from the existence of public communication between RW.06 Village. Kalisampurno through their respective RT, Rw.06 Village. Kalisampurno through the covid team and also through youths who live in the Rw.06 area. In addition to using public communication, the head of Rw.06 Village. Kalisampurno also spreads information about the covid pandemic through social media, especially whatsapp. With this, information can be spread to all residents of Rw.06 Village. Kalisampurno. This research is a type of quantitative research by choosing a location in the Rw.06 area of ​​Kalisampurno Village by distributing questionnaires through google form, totaling 110 respondents with random sampling technique. With data analyst using SPSS 20.0 . program. The results of this study indicate that the Group Communication variable (X1) partially and simultaneously has an influence on the Community Reception variable (Y) in the neighborhood area of ​​Rw.06 Village. Kalisampurno.